A Crucial Role for the Protein Quality Control System in Motor Neuron Diseases - Riccardo Cristofani; Valeria Crippa; Maria Elena Cicardi; Maria Elena Cicardi; Barbara Tedesco; Veronica Ferrari; Marta Chierichetti; Elena Casarotto; Margherita Piccolella; Elio Messi; Mariarita Galbiati; Paola Rusmini; et al. (Frontiers in Aging Neuroscience, 2020)
Motor neuron diseases (MNDs) are fatal diseases characterized by loss of motor neurons in the brain cortex, in the bulbar region, and/or in the anterior horns of the spinal cord. While generally sporadic, inherited forms linked to mutant genes encoding altered RNA/protein products have also been described. Several different mechanisms have been found altered or dysfunctional in MNDs, like the protein quality control (PQC) system. In this review, we will discuss how the PQC system is affected in two MNDs—spinal and bulbar muscular atrophy (SBMA) and amyotrophic lateral sclerosis (ALS)—and how this affects the clearance of aberrantly folded proteins, which accumulate in motor neurons, inducing dysfunctions and their death. In addition, we will discuss how the PQC system can be targeted to restore proper cell function, enhancing the survival of affected cells in MNDs.